Pengaruh Kualitas Pelayanan dan Promosi terhadap Kepuasan Konsumen pada Pizza Express Jakarta - Nizar Alam Hamdani (Jurnal Wacana Ekonomi, 2017)
The purpose of this study was to determine the effect of service quality and promotion on customer satisfaction at Pizza Express Jakarta. This research uses descriptive and verification methods. The respondents of this study were 96 respondents who were selected using incidental sampling techniques. The analysis technique used in this research is validity and reliability testing, descriptive analysis, classical assumption test, multiple linear regression, and hypothesis testing using SPSS. 20. The results showed that there was an effect of service quality on customer satisfaction at Pizza Express Jakarta. There is a promotional effect on customer satisfaction at Pizza Express Jakarta. And there is an effect of service quality and promotion on customer satisfaction at Pizza Express Jakarta. The conclusion of this research is that the formulation of the problem can be answered by the research hypothesis. So it is suggested to other researchers to conduct research with other variables which the author does not examine but affects this research such as; brand image, pricing, product quality and others.